A CuS-based chemical tongue chip for pattern recognition of proteins and antibiotic-resistant bacteria1. Issue 13 (14th February 2015) - Ran, Xiang; Pu, Fang; Ren, Jinsong; Qu, Xiaogang
<x xml:space="preserve">Abstract</x> A CuS-based sensor array having high stability and selectivity for identifying analytes on a quartz chip.